The Use of Video as a Learning Strategy in Supporting the Increasing Knowledge and Clinical Skills of Nursing Students - Indah Permata Sari; Sri Sundari (Universitas Muhammadiyah Semarang, 2021)
Video is a promising, relevant, and increasingly used form of learning media that can improve the quality of education. This study aims to further examine the use of video as a learning strategy in supporting the knowledge and clinical skills of nursing students. This study uses a quasi-experiment with pretest and posttest design to compare video methods and lecture methods in nursing students. The research sample population was 60 respondents and the research data collection method used the MCQ (Multiple Choice Question) questionnaire sheet for the assessment of the knowledge, while the OSCE (Objective Structured Clinical Examination) sheet for the assessment of students' clinical skills. Based on the results of research using paired t-test, posttest t-test, and hypothesis testing using independent sample t-test that the value of t count > t table (p-value = 0,000 <0.05), so that the value is significant in improving both aspects of the assessment. The video method has a higher average score and improvement than the lecture method.